Byatikramera eka adhyāẏa - Sultan, Syed Abdus (Runā Prakāśanī, 1981)
On the government and politics of Pakistan, 1958-1969, during the presidency of Mohammad Ayub Khan, b. 1907; personal narrative by a Bengalee lawyer.